The new modern philosophy : the inclusive anthology of primary sources - Marshall, Eugene (Routledge, 2018)
The seventeenth and eighteenth centuries are arguably the most important period in philosophy’s history, given that they set a new and broad foundation for subsequent philosophical thought. Over the last decade, however, discontent among instructors has grown with coursebooks’ unwavering focus on the era’s seven most well-known philosophers—all of them white and male—and on their exclusively metaphysical and epistemological concerns.　 While few dispute the centrality of these figures and the questions they raised, the modern era also included essential contributions from women—like Margaret Cavendish, Elisabeth of Bohemia, Mary Wollstonecraft, and Émilie Du Châtelet—as well as important non-white thinkers, such as Anton Wilhelm Amo, Julien Raimond, and Ottobah Cugoano. At the same time, there has been increasing recognition that moral and political philosophy, philosophy of the natural world, and philosophy of race—also vibrant areas of the seventeenth and eighteenth centuries—need to be better integrated with the standard coverage of metaphysics and epistemology.